From Chaos to Calm: Best Practices in Disaster Relief Blueprint for Relief: Good Governance in Humanitarian Efforts - Mohd Perdaus, Ahmad Faizal bin; Kharie, Mohamad Fadli bin; Hasan, Fauziah Mohd (International Journal of Human and Health Sciences (IJHHS), 2025)
Effective disaster relief requires a holistic approach that integrates good governance, innovative technologies, and ethical frameworks. This symposium explores best practices in disaster response, focusing on three critical areas: governance, cuttingedge technologies, and Islamic principles. Good governance ensures transparency, accountability, and coordination among stakeholders, from governmental bodies to humanitarian organizations. Emerging technologies, such as AI and data analytics, have transformed the speed and efficiency of disaster response, enabling more accurate resource allocation and real-time decision-making. Additionally, Islamic principles offer a valuable ethical framework for disaster relief, emphasizing compassion, community solidarity, and equitable aid distribution. Together, these three pillars provide a comprehensive model for improving the effectiveness of disaster relief efforts, promoting both short-term recovery and long-term resilience in affected communities. This symposium will foster a deeper understanding of the integrated strategies needed to enhance global disaster response. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S14